Heat shock protein 90α may serve as a biomarker for mild cognitive impairment in type 2 diabetes mellitus patients without diabetic nephropathy - Zhang, Hui; Chi, Meiyan; Feng, Songtao; Zhu, Wenwen; Wang, Hongxiao; Zhou, Wan; Song, Bing; Wang, Wei; Zhang, Haoqiang (Frontiers in Immunology, 2025)
AimChronic inflammation associated oxidative stress is a key factor in complications of type 2 diabetes mellitus (T2DM), including mild cognitive impairment (MCI), partly associated with cerebrovascular lesions including both macrovascular and microvascular changes, and diabetic nephropathy (DN), a kind of diabetic microvascular complication. Heat shock protein 90α (Hsp90α) is known to play a significant role in inflammation associated oxidative stress and DN. This study aims to explore the role of Hsp90α in MCI and its potential as a diagnostic marker for MCI in T2DM patients.MethodsWe included 119 T2DM patients and analyzed their clinical data, Hsp90α levels, and cognitive scores. The relationships among Hsp90α, cognitive function, and urinary albumin-to-creatinine ratio (UACR) were also examined. Binary logistic regression was used to identify MCI risk factors, and ROC curves assessed Hsp90α’s diagnostic value for MCI in patients, with or without DN.ResultsPatients with MCI exhibit worse cognitive function, higher UACR, and elevated Hsp90α levels compared to those without MCI. Increased Hsp90α was linked to lower cognitive scores and was identified as a risk factor for MCI. Patients with DN had a higher rate of MCI and cognitive decline than those without DN, and Hsp90α levels correlated with UACR, a DN marker. In patients without DN, higher Hsp90α was a risk factor for MCI; however, this was not observed in those with DN. An Hsp90α cut-off point of 69.105 ng/mL had a sensitivity of 60.0% and specificity of 91.4% for predicting MCI in patients without DN.ConclusionsElevated Hsp90α level is a risk factor for cognitive impairment and may serve as a biomarker for MCI in T2DM patients without DN.